Anti-furfurative comparison of Kesh Kanti-Herbal Shampoos and synthetic shampoos against Malassezia furfur for dandruff management - Acharya Balkrishna; Nem Kumar Ngpoore; Harshita Jonwal; Savita Lochab; Anurag Varshney (AMB Express)
Abstract Malassezia furfur is the primary etiological agent of dandruff (Pityriasis capitis). Although herbal shampoos are preferred for their natural, mild ingredients over synthetic counterparts, they are often perceived as less effective in managing flaky scalp conditions or furfuration causing dandruff. The study compares the antifungal efficacy of herbal and synthetic shampoos against M. furfur. Seven shampoos including herbal (HS_Adv, HS_M&P, HS_Aloe), synthetic (SYN_01, SYN_02, SYN_03) and an antifungal shampoo containing ketoconazole (KETO) were employed in the study. Experiments were designed to stimulate real-world conditions, utilizing disc-diffusion assay, 3-minute shampoo contact at mild dilutions (1% and 5%), recurrent 3-minute shampoo contact every 24 h with intermittent recovery. Both disc diffusion and 3-minute shampoo contact demonstrated that all shampoos were effectively inhibiting the viability of M. furfur. However, a single 3-minute shampoo contact followed by a prolonged recovery of 72 h revealed SYN_01 and KETO with maximal antifungal action. In contrast, herbal shampoos were as effective as synthetic options when M. furfur was subjected to 3-minute shampoo contact every 24 h with intermittent recovery. Comprehensive ingredient analysis revealed the robust antifungal activity in SYN_01 was probably because of the presence of various surfactants, allergens and a potent synthetic antifungal agent, Piroctone olamine. This study experimentally demonstrates that herbal shampoos are as effective as synthetic options in managing M. furfur-induced dandruff when applied consistently. The findings highlight the importance of regular scalp cleansing for dandruff management and provide valuable insights into the antifungal potential of both herbal and synthetic formulations.